Perlindungan Hukum Jamu Tradisional sebagai Kekayaan Intelektual Komunal di Indonesia - Yoga Deswat; Liza Marina (Universitas Medan Area, 2026)
Traditional herbal medicine (jamu) represents a form of traditional cultural expression (TCE) and communal intellectual property (CIP) passed down through generations, carrying cultural, health, and economic significance. However, Indonesia’s current legal system does not provide adequate protection for jamu as a collective cultural product, as it remains based on individual intellectual property models. This research aims to analyze weaknesses in national regulations, assess the relevance of international instruments such as the Convention on Biological Diversity, the Nagoya Protocol, and UNESCO 2003, and propose a regulatory reconstruction model that is more comprehensive and contextual. The method used is normative juridical with statutory, conceptual, and comparative approaches. Findings show the urgency for a specific law to regulate legal protection of TCEs and CIP, along with the integration of international principles like prior informed consent and benefit sharing into national law. Therefore, the protection of jamu as intangible cultural heritage can be more just, sustainable, and community-centered.